Determinants of financial worry of widows and widowers compared to married individuals - Krausman, Jodi Grace (Kansas State University, 2024)
This study explores financial stress and how it can manifest into financial worry. Financial worry is defined as “repeated and negative thinking about the uncertainty of one’s (future) financial situation” (de Bruijn & Antonides, 2020, p. 1). Money issues and relationship hurdles can create financial stress, which can lead to uncertainty and financial worry (Magwegwe et al., 2020). So, too, can relationship status and gender (Hsu & Barrett, 2020). Financial stress, or the “level of stress and well-being emanating from one’s personal financial condition” (Prawitz et al., 2006, p. 36), can differ for married and widowed individuals. Widowed individuals may experience added personal grief along with increased financial pressures due to the loss of income, responsibility for overseeing all financial matters for the first time, or lack of an emergency fund. This study seeks to identify differences in financial worry between heterosexual married individuals and widows/widowers. It utilizes the Stress Process model (Pearlin et al., 1981) to investigate stressful financial indicators, personal resources, and financial resources by comparing the financial statuses of married and widowed individuals (Pearlin et al., 1981). Data provided by the National Financial Capability Study (NFCS) in 2018 was used to measure financial stress for U.S. adults above the age of 45. The NFCS includes questions on objective and subjective financial stressors (e.g., paying bills on time, calls from collection companies, debt levels, etc.), the consequences of which were expected to result in financial worry measured with a six-component index. This study also utilized structural equation modeling to identify differences in financial stress levels between married and widowed individuals. While the study found no significant difference between married and widowed individuals in fueling financial worry, it did discover that subjective financial stressors (e.g., what married and widowed individuals thought about their present financial situation) were significantly different when compared to objective financial stressors (e.g., drop in income, debt levels, inability to pay bills). The study also found that objective financial stressors are significant for married individuals and that personal resources matter significantly. An understanding of the determinants of financial worry can help financial practitioners and financial educators create plans and strategies for clients coping with financially stressful situations. This study will be especially useful for financial planners, financial counselors, and financial therapists who work both with married and widowed individuals.
Keywords: Financial stress; Objective/subjective financial knowledge; Widows/Widowers; Married individuals